EDUCATION ON FOOD ADDITIVES IN SCHOOL SNACKS FOR STUDENTS AND TEACHERS AT SMAN 11 BANDUNG - Gozaly, Thomas; Rukmana, Jaka; Marthia, Nabila; Mulia, Rizqan Karima; Qhaleed, Shahnaz Naurelia Idhna (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2025)
This community service activity aimed to address the high consumption of snacks containing food additives (BTP) among students who lack sufficient understanding of their types, functions, and health impacts. Many school-sold snacks use artificial colors, preservatives, or sweeteners that may exceed the limits set by the Food and Drug Administration (BPOM). To respond to this issue, lecturers from the Department of Food Technology, Universitas Pasundan, conducted educational outreach at SMAN 11 Bandung to enhance food literacy—especially in recognizing and managing the presence of BTP in school snacks. The outreach was delivered interactively through presentations, group discussions, simulations of reading BTP information on packaging labels, and distribution of educational leaflets. Key materials included: types of commonly used food additives, health risks of excessive BTP consumption, BPOM regulations, identification of BTP through E-numbers and packaging labels, and promotion of local foods and healthy snack alternatives. The activity was well-received by students and staff. Participants showed high enthusiasm, demonstrated by active engagement and many questions during discussions. Teacher involvement also suggested potential for ongoing knowledge dissemination within the school community. As tangible outputs, the team produced a final activity report, two popular articles submitted to national media, and video documentation to be used as teaching materials and promotional tools for similar educational initiatives in other schools.